Репрезентація у Великій українській енциклопедії дослідників архітектури Сіверщини - Вечерський, В.В. (Сіверщина в історії України, 2023)
Стаття присвячена питанням репрезентації конкретних персоналій у Великій українській енциклопедії – державному енциклопедичному проєкті, що реалізується з 2013 р. як енциклопедія універсального характеру у вигляді багатотомного видання і одночасно – вебпорталу. Авторові цієї статті як історику архітектури й досліднику важливого історичного регіону Сіверщини цікаво було простежити за тим, щоб найвизначніші попередники й колеги – дослідники архітектури цього регіону – були гідно представлені в енциклопедії. Таких персоналій, що відповідають заздалегідь визначеним універсальним критеріям, виявилося близько двох десятків (у статті подано повний їх перелік). Усіх їх об’єднує спільна риса – вони досліджували архітектуру не однієї лише Сіверщини, а й усієї України, а деякі – і всесвітню історію архітектури. Такий погляд на архітектуру Сіверщини – у широкому світовому контексті – забезпечує непроминальну наукову вартість цих досліджень з дотриманням балансу між універсальним, національним і регіональним. The article is devoted to the issues of representation of specific personalities in the Great Ukrainian Encyclopedia - a state encyclopedic project that has been implemented since 2013 as a universal encyclopedia in the form of a multi-volume publication and at the same time - a web portal. The author of this article, as an architectural historian and researcher of an important historical region of Siver region, was interested in ensuring that the most prominent predecessors and colleagues - researchers of the architecture of this region - were adequately represented in the encyclopedia. There were about two dozen such personalities that correspond to predetermined universal criteria (a full list of them is presented in the article). All of them have one thing in common - they studied the architecture of not only Siver region, but also of all of Ukraine, and some of them studied the world history of architecture. Such a view of the architecture of the Siver region - in a broad world context - ensures the infallible scientific value of these studies, while maintaining a balance between universal, national and regional. Considering the prospects of further encyclopedic research in the field of architectural monuments, it is possible to express the hope that in the future «Ukrainian Architectural Encyclopedia!» the personalities of researchers of the architecture of the Siver region will be presented much more fully.